(untitled) (Research, Society and Development, 2023)
Digital education can be a useful tool to help address the shortage of nurses. Digital education can provide students with access to information in an accessible and quick manner, making it ideal for those who do not have access to in-person education. The aim of this work is to describe how digital education can address the shortage of nurses in the United States. The study was conducted through a descriptive and qualitative literature review. Digital education can be a useful tool to help address the shortage of nurses. Digital education allows students to learn quickly and easily and is especially useful for those who do not have access to in-person courses. Additionally, digital education can help reduce the costs associated with nurse training, allowing more people to have access to education. Digital education can also be used to provide students with updated information on best nursing practices and ensure that qualified nurses are prepared to deal with changes in the healthcare sector. However, it is important to remember that digital education is only a partial solution to the shortage of nurses. Furthermore, it is important that digital nurse training programs are of high quality and offer students the opportunity to acquire practical skills and develop adequate clinical competencies.